Rbm45 Phylogenetics, Protein Domain Conservation, and Gene Architecture in Clade Metazoa - Virdjinija Vuchkovska; Teagan N. Marti; Anali Cisneros; Lauren M. Saiki; Jeffrey O. Henderson (Journal of Evolutionary Science, 2024)
Mammalian Rbm45 is predominately expressed in neuronal tissue and is integral in brain development and neuronal differentiation under physiological conditions. Dysregulation of Rbm45 has been strongly associated with neurodegenerative disorders in humans and can drive hepatocellular carcinoma through reprogramming lipid metabolism. Intriguingly, Rbm45 is an ancient protein, evolutionarily conserved throughout metazoans, including in sponges which lack a nervous system. Curiously, the evolution of Rbm45 gene structure and protein domain conservation across kingdom Animalia is largely unknown. We performed phylogenetic analysis of Rbm45 nucleotide and amino acid sequences from 36 species representing 9 phyla: Porifera, Cnidaria, Priapulida, Mollusca, Brachiopoda, Arthropoda, Echinodermata, Hemichordata, and Chordata. While the tree from Rbm45 nucleotide sequence data resulted in clades Protostomia and Deuterostomia showing paraphyly, the phylogeny derived from Rbm45 amino acid sequence largely recapitulated known monophyletic relationships among metazoans. Human RBM45 protein structure includes three RNA-binding domains (RBD), a homo-oligomerization association (HOA) domain, a nuclear localization sequence (NLS), and a nuclear export sequence (NES). Multiple sequence alignment across the same 36 taxa used for phylogenetic analysis revealed conservation of all three RBDs, the HOA, and NLS; in contrast the NES was only detected in clade Craniata and not in clades Ambulacraria and Protostomia. Rbm45 gene structure analysis revealed increasing gene complexity concomitant with increasing evolutionary complexity. Rbm45 from non-bilaterian taxa had from 2 to 4 large exons, while bilaterian taxa had between 6 to17 small exons. These findings demonstrate that Rbm45 is an ancient, highly conserved gene among metazoans suggesting a function in a breadth of neural/sensory systems.
Keywords: Rbm45